2018
DOI: 10.1007/s00586-018-5505-4
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative K-line conversion from negative to positive is independently associated with a better surgical outcome after posterior decompression with instrumented fusion for K-line negative cervical ossification of the posterior ligament

Abstract: Postoperative K-line conversion from (-) to (+) is a factor independently associated with a better surgical outcome. These slides can be retrieved under Electronic Supplementary material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Koda et al reported that K-line conversion from negative to positive is associated with better neurological outcomes. 31 Likewise, the results of the present study showed that conversion of mK-line status is associated with a recovery rate ≥50%. Second, since VBSO is a fusion procedure, ROM is eliminated at the pathologic segments.…”
Section: Discussionsupporting
confidence: 71%
“…Koda et al reported that K-line conversion from negative to positive is associated with better neurological outcomes. 31 Likewise, the results of the present study showed that conversion of mK-line status is associated with a recovery rate ≥50%. Second, since VBSO is a fusion procedure, ROM is eliminated at the pathologic segments.…”
Section: Discussionsupporting
confidence: 71%
“…As K‐line (−) was converted to K‐line (+) using PDF with VP, sufficient ventral and posterior decompression were met, which led to better outcomes than conventional PDF in the K‐line (−) case. To the best of our knowledge, the recovery rate for K‐line (−) patients approximately ranges from 54% to 73% after ADF and 38.2% to 43.6% after PDF 8,9,24,25,30,31 . Our study showed an average recovery rate of 70.59% in the JOA score of all cases, 72.08% in kyphotic cases, and 70.51% in thick OPLL (MOR>50%), which is acceptable as K‐line (−) indicates poor clinical prognosis (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…6,7 Postoperative K-line conversion from negative to positive is associated with a better surgical outcome. 8 OPLL is primarily found in the cervical spine and is a common pathogeny of cervical myelopathy. 9,10 Most patients with C-OPLL do not exhibit any neurological symptoms in the early stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported poor postoperative neurologic improvements after laminoplasty in patients with Kline (−) OPLL [25]. The mean recovery rate of the K-line (−) OPLL patient group was significantly lower than that of the K-line (+) group.…”
Section: Discussionmentioning
confidence: 88%